MULTIVARIATE PRINCIPAL COMPONENT ANALYSIS OF MORPHOLOGICAL TRAITS IN WEST AFRICAN DWARF GOATS (FUDMA JOURNAL OF SCIENCES, 2020)
Multivariate analysis are important tools when considering all variables simultaneously. Principal component analysis using morphological variables of the West African Dwarf goats of Nigeria were carried out based on age and sex. A total of 250 goats, comprising of 143 does and 107 bucks, were used for this study. Data were collected from 10 morphological traits, including; body weight (BWT), body length (BL), height at wither (HW), rump height (RH), paunch girth (PG), heart girth (HG), ear length (EL), tail length (TL), horn length (HoL) and neck circumference (NC). Data collected were subjected to analysis procedures of SPSS (2011) statistical programme. Majority of the goats sampled were female indicating goat keepers’ preference for female than male for herd multiplication. Results of the ANOVA obtained revealed that sex had significant (P
Keywords: Age, goats, morphometric traits, principal components, sex.